Frequency of Bicytopenia in Slide-Positive Malaria Patients - Bakht, Khush; Khan, Raza Muhammad; Khan, Shahtaj (Indus Journal of Bioscience Research, 2025)
Background: Malaria is a life-threatening parasitic disease that remains a significant global health concern, particularly in endemic regions. Haematological abnormalities such as bicytopenia, characterised by the reduction of two blood cell lines (red blood cells, white blood cells, or platelets), are commonly observed in malaria patients. Methodology: A cross-sectional study was conducted over six months at the Department of Hematology, Hayatabad Medical Complex, Peshawar. A total of 138 patients, aged 16–60 years, with confirmed Plasmodium falciparum or Plasmodium vivax malaria, were included. Bicytopenia was defined as a white blood cell count below 3,000/cmm and a platelet count below 150,000/mm³. Data on demographic, clinical, and laboratory parameters were collected and analysed using SPSS version 23. Stratification and post-stratification analyses were performed to identify significant associations, with a p-value <0.05 considered statistically significant. Results: Bicytopenia was observed in 32% of malaria patients. The most common pattern involved a reduction in white blood cells and platelets (91%), followed by a combination of white blood cells and red blood cells (7%), and platelet and red blood cell reduction (2%). Patients with bicytopenia were more likely to report symptoms such as fatigue (80%, p=0.048) and easy bruising (45%, p<0.001). Plasmodium falciparum was more frequently associated with bicytopenia compared to P. vivax, although the difference was not statistically significant (p=0.126). Laboratory findings showed significantly lower haemoglobin levels, white blood cell counts, and platelet counts in the bicytopenia group compared to the non-bi-cytopenia group (p<0.001 for all). Conclusion: This study highlights a significant burden of bicytopenia among malaria patients, with P. falciparum being a major contributor. The findings emphasise the importance of routine haematological evaluations in malaria management to identify and mitigate complications early.